1993
DOI: 10.1161/01.atv.13.1.48
|View full text |Cite
|
Sign up to set email alerts
|

Fibrinogenolytic and fibrinolytic activity of cell-associated plasmin.

Abstract: Binding of plasmin (ogen) to rat C6 glioma cells is saturable and kringle-domain dependent. This interaction was studied as a model of plasimin(ogen) receptor interactions in nucleated mammalian cells. Apparent l25 I-plasmin dissociation from OS cell binding sites was slow; however, the dissociation rate was increased when the solution contained diisopropyl phosphoryl-plasmin (0.3 juM), fibrinogen (0.16 or 0.8 mg/ml), 1.08 mM D-Val-L-Leu-L-Lys-p-nitroanilide-HCl (S-2251), or e-amino-n-caproic acid (EACA, 5.0 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

1993
1993
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…Since local ized fibrinolysis reflects rather the site of concentration of PAs than the systemic fibrinolysis potential, we aimed to characterize the fibrinolyt ic activity of the cRA-treated C6 glioma. Moreover, it has been already suggested that C6 glioma cell-line, which is considered as a model of peri-cellular fibrinolytic activity (3,4,5), produced PAs. Expression and activity of such serine protease has never been thoroughly explored (13), but could explain the localized tumoral fibrinolysis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since local ized fibrinolysis reflects rather the site of concentration of PAs than the systemic fibrinolysis potential, we aimed to characterize the fibrinolyt ic activity of the cRA-treated C6 glioma. Moreover, it has been already suggested that C6 glioma cell-line, which is considered as a model of peri-cellular fibrinolytic activity (3,4,5), produced PAs. Expression and activity of such serine protease has never been thoroughly explored (13), but could explain the localized tumoral fibrinolysis.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, it was sug gested that spontaneous tumor brain haemorrhage may be due to a lo cally enhanced fibrinolytic activity which may be aggravated by tumor necrosis and vessel rupture (2). Although plasminogen activators (PAs) produced by C6 cells are not yet characterized, the C6 cell-line is a very characteristic model for fibrinolytic activity of cell-associated plasmin (3,4,5). C6 glioma cells produce in vivo a proteolytic activity related mainly to type IV collagenase (6 ), which is derived from its precursor by activation by plasmin (7).…”
Section: Introductionmentioning
confidence: 99%
“…In the presence of 10 mM EACA, the majority of the APSAC (80-90%) was rapidly recovered in solution. EACA accelerates plasminogen dissociation from cell surfaces in addition to preventirg reassociation (18). EACA probably affects cell-associated APSAC similarly.…”
Section: Apsac Dissociation From Cellular Binding Sitesmentioning
confidence: 99%
“…For determination of the related signalling pathways, PKI (protein kinase A inhibitor, 10 nM) and U0126 (ERK inhibitor, 2 μM) were used to treat astrocytes for 3 hrs before exposure to DOF extracts, forskolin (10 μM), and TPA (100 nM) (Cao et al, 2018). To evaluate the effect of DOF extracts on neurotrophic factor synthesis, EACA (plasminogen inhibitor, 5.0 mM) and JNJ0966 (MMP-9 inhibitor, 0.4 μM) were used to treat astrocytes for 24 hrs before exposure to DOF extracts (Humphries, Vasudevan, & Gonias, 1993). PC12 cell lines were used to evaluate the ability of DOF extracts to promote neuronal differentiation.…”
Section: Drug Treatmentmentioning
confidence: 99%